Crop and non-crop productivity in a traditional maize agroecosystem of the highland of Mexico - Martínez-Bernal Angélica; Basurto-Peña Francisco; González-Amaro Rosa; Vibrans Heike (BMC, 2009)
Abstract Background In Mexico, the traditional maize cultivation system has resisted intensification attempts for many decades in some areas, even in some well-connected regions of the temperate highlands. We suggest that this is due to economics. Methods The total useful biomass of several fields in Nanacamilpa, Tlaxcala, are evaluated for productivity and costs. Results Maize grain production is low (1.5 t ha-1) and does not cover costs. However, maize stover demands a relatively high price. If it included, a profit is possible (about 110 US $ ha-1). We show that non-crop production (weeds for food and forage) potentially has a higher value than the crop. It is only partially used, as there are constraints on animal husbandry, but it diversifies production and plays a role as a back-up system in case of crop failure. Conclusion The diversified system described is economically rational under current conditions and labor costs. It is also stable, low-input and ecologically benign, and should be recognized as an important example of integrated agriculture, though some improvements could be investigated.